Comparison of retention of posterior class i composite resin fillings done by two different incremental and bulk fill techniques - Manan, Abdul; Shehzad, Aamir; Sadaqat, Saveela; Hussain, Ashar; Rizwan, Muhammad; Umar, Muhammad Bin (Journal of University Medical & Dental College, 2026)
BACKGROUND AND OBJECTIVES: Use of Composite fillings is a common and preferred practice in dentistry. Dental surgeons use various techniques to get maximum retention and better aesthetics using composite resins. The purpose of our study was to compare the retention of posterior class I fillings of composite resin fillings using increments and single-placement techniques. METHODOLOGY: This randomized control trial study (No. #3336-R-A25) was conducted at the Restorative Department of Frontier Medical and Dental College, Abbottabad, from 10th July 2024 to 10th January. 2025. It consisted of 104 participants with occlusal class I cavities of at least 3mm deep. The Filtek Z250 (3M, ESPE) filling material was used in two restorative techniques (incremental and single-fill). Patients were divided into two groups, A and B, each of 52 participants. In Group A, the incremental filling technique was used; in Group B, the single filling technique was used. After 6 months, filling retentions were evaluated. Data was analyzed by using SPSS version 23. RESULTS: After 6 months, 90.4% retention, 9.6% non-retention, and 0% partial loss in the incremental group, whereas 84.6% retention, 9.6% non-retention, and about 5.8% partial loss in the single-fill group were observed (Figure I). It showed no statistically significant difference in retention between the two groups using two different techniques (p > 0.374). CONCLUSION: This study showed that the retention of incremental fill composite is almost equal to that of the single fill resin in class I fillings of posterior teeth. It is mainly the skill of a dental surgeon in performing composite fillings with perfection, following the protocol and the manufacturer’s instructions.